Epidemiological Patterns of Skin Disease in Saudi Arabia: A Systematic Review and Meta-Analysis - Mohammad Almohideb (Hindawi Limited, 2020)
Background. Large epidemiological studies on patterns of skin diseases in Saudi Arabia are scarce. Therefore, this systematic review and meta-analysis was conducted to gather available epidemiologic data describing the pattern of skin diseases in different geographical areas in Saudi Arabia. Methods. A comprehensive literature search of articles was conducted in PubMed, SCOPUS, and Web of Science through October 2019. We included all published cross-sectional studies that provided data on relevant incidence or prevalence of skin disease in Saudi Arabia. The risk of bias within the included cross-sectional studies was assessed using the Hoy tool for the prevalence studies. All statistical analysis was performed using the Comprehensive Meta-analysis software. Results. The present meta-analysis included 14 studies that reported the frequency of the skin disease patterns in different regions in Saudi Arabia with a total sample size of 30436 patients with an overall low risk of bias. The diseases of skin appendages and dermatitis were the most commonly reported skin diseases in Saudi Arabia (24.8% (95% CI, 24.3-25.3) and 24% (95% CI, 23.6%-24.6%), respectively). Skin infection represented about 18.5% (95% CI, 18.1%-19%), while the papulosquamous disorders represented 5.3% (95% CI, 5%-5.6%) of the skin diseases in Saudi Arabia. Skin cancers were pooled from only two studies. Basal cell carcinoma and squamous cell carcinoma were the most common malignant neoplasm in Saudi Arabia (51.4% and 22.5% of the malignant neoplasm, respectively), while malignant melanoma represents only 3.8% of the malignant skin cancer. Conclusion. Adnexal disorders and dermatitis are the most common skin disease in Saudi Arabia, followed by skin infection and pigmentary disorders. While skin cancer is more frequent than other countries, awareness campaigns should be initiated to increase knowledge about the harmful effect of long-term sun exposure.